THE IMPLEMENTATION OF INTERNAL QUALITY ASSURANCE (IQA) IN THREE PRIVATE UNIVERSITIES IN SAMARINDA - E. Elbadiansyah; M. Masyni (Erudio Journal of Educational Innovation, 2021)
Sistem Penjaminan Mutu Internal (SPMI) or the Internal Quality Assurance (IQA) in three private universities in Samarinda has been implemented using Perencanaan, Pelaksanaan, Evaluasi, Pengendalian, dan Peningkatan (PPEPP) or Planning, Implementation, Evaluation, Control, and Improvement, including evaluating control and improvement of Higher Education standards. This study was conducted with the following objectives. First, it described the implementation of IQA in evaluating control and improvement of higher education standards in three private universities in Samarinda. Second, it explained the inhibiting factors and proposed possible solutions. The data of this qualitative study were collected through (1) in-depth interviews, (2) observations, (3) photographs, and (4) documentation. The data went through interactive transformation data analysis proposed by Miles and Huberman (1994), including data collection, data reduction, data presentation, and conclusion. The validity of the data included data credibility, transferability, dependability, and confirmability. Findings confirmed the followings. First, the implementation of IQA was not yet optimal in evaluating control and improvement of the higher education standards as mentioned in the ministerial regulation of the Research, Technology, and Higher Education Ministry Number 62 of 2016 Article 5 Paragraph 1 and Number 44 of 2015 concerning the National Higher Education Standards. Second, the inhibiting factor was related to the inadequate management of the Standard Operating Procedure (SOP) and follow-up plans for internal quality audits, outputs, and achievements. The solutions proposed in this study included conducting follow-up plans and improving the learning process SOP, the lesson planning SOP, class schedule, and learning outcomes. Essential documents should always be made available, including semester program documents, Satuan Acara Perkuliahan (SAP) or Course Units, and lecturing schedules to achieve sustainable quality improvement in three private universities in Samarinda.